(untitled) (UNIHumanitas, 2019)
This work had the objective of determining the participation of International Organizations in the intervention in the Middle East conflicts due to the proliferation of nuclear weapons. The literature review included searching for articles in journals and on the official website of the United Nations since 2006, reading and analyzing the materials, selecting two of the ten essential references to explain the definition of nuclear weapons, the political, military and civil crises and conflicts that it brings about and thus generate possible strategies to end the dangers of the Middle East. After the analysis carried out, it can be mentioned that the Syrian Spring and the intense humanitarian crisis in Yemen have been one of the main causes for States from different parts of the world to direct their attention towards this area, intervening in incorrect ways and leaving their cooperation available to others, who in question are not reliable. Given this situation, the need to find effective methods that generate greater stability in the area, mainly based on International Law and the principle of non-intervention, is highlighted.